1992
DOI: 10.1002/acp.2350060407
|View full text |Cite
|
Sign up to set email alerts
|

Elaborative interrogation applied to small and large group contexts

Abstract: The present study examined the application of elaborative interrogation (EI), a questioning strategy, to ecologically valid classroom contexts. Instruction was provided to individuals, small groups of five, and large groups of 20. Recall performance did not differ as a function of group size. For individuals, small and large groups, EI subjects outperformed repetition control subjects.Acquiring facts is an important but often difficult educational requirement, one made easier by a verbal learning strategy call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Researchers found greater retention with EI strategies in young learners , adolescents (Wood, Willoughby, Kaspar, & Idel, 1994), and adults (Pressley et al, 1988), regardless of presentation formats such as isolated facts (Pressley et al, 1988), sequential facts (Willoughby et al, 1993), paragraphs versus isolated facts (Woloshyn, Willoughby, Wood, & Pressley, 1990), and paragraphs (Seiffert, 1993). EI is a versatile strategy that has been taught explicitly to learners (Wood, Fler, & Willoughby, 1992) and implemented as a text supplement for learners (e.g., Boudreau, Wood, Willoughby, & Sprecht, 1999;Seiffert, 1993).…”
mentioning
confidence: 99%
“…Researchers found greater retention with EI strategies in young learners , adolescents (Wood, Willoughby, Kaspar, & Idel, 1994), and adults (Pressley et al, 1988), regardless of presentation formats such as isolated facts (Pressley et al, 1988), sequential facts (Willoughby et al, 1993), paragraphs versus isolated facts (Woloshyn, Willoughby, Wood, & Pressley, 1990), and paragraphs (Seiffert, 1993). EI is a versatile strategy that has been taught explicitly to learners (Wood, Fler, & Willoughby, 1992) and implemented as a text supplement for learners (e.g., Boudreau, Wood, Willoughby, & Sprecht, 1999;Seiffert, 1993).…”
mentioning
confidence: 99%
“…Learning gains were obtained with varying presentation formats (paragraph versus isolated facts; Woloshyn et al, 1990;paragraphs;Seifert, 1992; sequential facts, Willoughby, Waller, Wood, and MacKinnon, in press) and in diverse study contexts (e.g. individual versus group instruction; Wood, Fler, and Willoughby, 1992).…”
mentioning
confidence: 99%
“…Previous research supports the suggestion that students asked to employ elaborative interrogation may spontaneously use alternative strategies in addition to elaborative interrogation while studying. For example, students' self-reports indicated that elaborative interrogation also led to the use of imagery, mnemonic, and other sophisticated procedures (Wood, Fler, & Willoughby, 1992). Perhaps, as Siegler (1998) suggests, when a complex strategy is first acquired, it is often used in conjunction with other strategies.…”
Section: Discussionmentioning
confidence: 99%